Does "Good" Corporate Governance Help in a Crisis? The Impact of Country‐ and Firm‐Level Governance Mechanisms in the European Financial Crisis. (13th December 2012) - van, Marc; Engelen, Peter‐Jan; Carney, Michael
Abstract Manuscript Type Empirical Research Question/Issue We examine the effects of firm‐ and country‐level "good" corporate governance prescriptions on firm performance before and during the recent financial crisis, using a large sample of 1, 197 firms across 26 European countries. Research Findings/Insights We propose a contextualized agency perspective suggesting that firm‐ and country‐level good governance prescriptions designed to assure managerial oversight may not hold in a financial crisis. This is because firms can benefit from broadening managerial discretion so as to facilitate the exercise of initiative and decisive leadership. Overall, our firm‐ and country‐level findings support this argument. In a crisis, CEO duality is associated with better performance. We also find that the use of incentive compensation and the existence of a wedge between ownership and control rights negatively impacts on firm performance in a crisis. Hierarchical linear modeling shows that 25 percent of the heterogeneity in firm performance is among countries, indicating the importance of including country‐level institutions in our analyses. In a crisis, we find that the general quality of the legal system and creditor rights protection are positively related to firm performance, but protection for equity investors is not. Theoretical/Academic Implications The findings challenge the universality of good governance prescriptions and contribute to the growing body of work proposing that the efficacy of governance mechanisms may be contingent upon organizational and environmental circumstances. Practitioner/Policy Implications The study offers insights relevant to policy and practitioner communities, showing that governance mechanisms operate differently in crisis and non‐crisis periods. The tendency to respond to a crisis with more stringent rules may be counterproductive since such measures may compromise executives' ability to respond appropriately to systemic shocks. Practitioners are encouraged to optimize rather than maximize their governance choices.